2013
DOI: 10.1002/ptr.4925
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP‐activated Protein Kinase and Phosphorylation of Glycogen Synthase Kinase3 β Mediate Ursolic Acid Induced Apoptosis in HepG2 Liver Cancer Cells

Abstract: Despite the antitumour effect of ursolic acid observed in several cancers, the underlying mechanism remains unclear. Thus, in the present study, the roles of AMP-activated protein kinase (AMPK) and glycogen synthase kinase 3 beta (GSK3β) were examined in ursolic acid induced apoptosis in HepG2 hepatocellular carcinoma cells. Ursolic acid significantly exerted cytotoxicity, increased the sub-G1 population and the number of ethidium homodimer and terminal deoxynucleotidyl transferase(TdT) mediated dUTP nick end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…UA-mediated ATP depletion induces energy stress that resulted in AMP-activated protein kinase (AMPK) activation in breast cancer cells that in turn promoted cytotoxic autophagy and apoptosis (this study). UA-induced AMPK activation also contributed to growth inhibition and apoptosis in T24 bladder cancer cells [50] and hepatoma HepG2 cells [51, 52], and autophagy in U87MG glioma cells [37]. More recently, AMPK was found to be a negative regulator of aerobic glycolysis and a suppressor of tumor growth in vivo [53].…”
Section: Discussionmentioning
confidence: 99%
“…UA-mediated ATP depletion induces energy stress that resulted in AMP-activated protein kinase (AMPK) activation in breast cancer cells that in turn promoted cytotoxic autophagy and apoptosis (this study). UA-induced AMPK activation also contributed to growth inhibition and apoptosis in T24 bladder cancer cells [50] and hepatoma HepG2 cells [51, 52], and autophagy in U87MG glioma cells [37]. More recently, AMPK was found to be a negative regulator of aerobic glycolysis and a suppressor of tumor growth in vivo [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that UA activates the AMPK pathways in both primary and cancer cells but exerts apoptosis in cancer cells and protects cell death in primary cells . Likewise, UA also induces apoptosis in stellate cells .…”
Section: Discussionmentioning
confidence: 99%
“…Ramos et al (2008) found that UA prevented DNA damage via increase of DNA repair and anti-proliferative properties in HepG2 cells. Lin et al (2011) found that UA reversed the invasion and migration of Hep3B and Huh7 cell lines at 4 lmol/ L. Son et al (2013) reported that UA blocked HepG2 cellular metabolism via AMPK activation and GSK3b phosphorylation, and thus induced apoptosis of HepG2 cells. On the suppression of carcinogenic side, UA could prevent HCC from nonalcoholic fatty liver disease (NAFLD), insulin resistance, inflammation and oxidation stress.…”
Section: Introductionmentioning
confidence: 98%